Las relaciones Estado-Ciudadanos en la reestructuración del Bienestar. Revisión conceptual para un análisis crítico de la Política Social - Espadas Alcázar, M.ª Ángeles (Cuadernos de Trabajo Social, 2007)
During the two last decades, an important part of the debate on Social Policy has been around the articulation tools for State-citizens relationships and, more specifically, around the promotion of their role in the Public Policies development. In this context, in the field of Social Services and Social Work, it is common to find some concepts that, even if they share the generic approach of expanding the role of citizens and their organizations, correspond, however, to different (or even divergent) theoretical models of Social Policy. In this article, the review of some concepts related to the citizens’ways of participation is suggested in order to show the capabilities and limitations that using each of them as reference points imply. In our opinion, the clarification of the fundamental conceptual referents is needed in order to have a solid foundation of the critical perspectives that defend transformative social intervention models that won’t involve the cancellation of the Welfare model but its participative reinvention.